Pivots, pirouettes and practicalities: Actions and reactions of work-integrated learning practitioners - Connor, Melissa; Mueller, Beate; Mann, Samuel; Andrew, Martin (Journal of University Teaching and Learning Practice, 2021)
One impact of the global pandemic of 2020 was a rapid shift in the delivery of work-integrated learning (WIL) to remote activity among WIL practitioners, students and educators alike. Along with professional practice research in higher degrees, WIL practice, including placements and non-placements, responded actively and sometimes reactively to the challenges of sudden transition to online environments. What strategies - pivots and pirouettes - did WIL practitioners use to weather the storm of Covid-19? What does this tell us about the nature of WIL? This paper captures the seemingly overnight response to shifting work-based learning to online and other spaces. With change came the opportunity to reflect on the varying areas of WIL: from the practical processes of ensuring students are cared for to pivoting to the learning opportunities it presented in building digital literacies and adapting to the global future of work. This study is a Trans-Tasman collaboration of four WIL practitioners exploring their responsiveness to disruption in WIL contexts. We present collective autoethnographic responses to such themes as disruption, becoming resilient, pivoting to change, changing perceptions of WIL and the legacies of the pandemic. These themes apply to learners and educators alike, and our words embody the experiences of both groups. Our responses to phenomena highlighted this need for resilience and agility. Methodologically, the researchers’ micro-narrative responses to key themes structure themselves into a macro-narrative that demonstrates the lived experiences of the researchers as educators in the WIL space and explores implications for ongoing and future practice.